A theoretical approach in evaluating the potential impact of women telecommuters on travel demand - Mustafa, Mootaz Munjid; Kadar Hamsa, Abdul Azeez (2010)
A number of Malaysian cities are experiencing severe transport problems resulting from rapidly increasing vehicle ownership and usage, and the insufficient supply and inferior quality of public transportation. As a result, supply of transport facilities is constantly lagging behind the level of transport demand. The trend of congestion, frequent traffic accidents and air pollution is no where more prevalent than in the Kuala Lumpur metropolitan area. Telecommuting is increasingly being perceived as a viable travel demand management strategy. Due to a number of travel patterns and characteristics that are unique to women commuters and the relatively large participation rate of women in the Malaysian work force, telecommuting by women workers seems a more relevant and potentially more crucial means of alleviating rush hour traffic in the Kuala Lumpur metropolitan area. The aim of this study is to investigate both the actual and potential impacts of involving women workers in the practice of telecommuting on travel demand and rush hour traffic in Kuala Lumpur. However, this paper highlights the literature background on women workforce in Malaysia, vehicle growth and associated travel pattern, and elements related to initial stage of this study.